Late discovery of a case of testicular feminisation. - Schindler, A M (1978)
The accidental discovery, in an inguinal hernia, of a male gonad in a 67-year-old woman is reported. The association of an unambiguous female phenotype with a purely male karyotype and a male gonad suggests the diagnosis of testicular feminisation. The differential diagnosis, particularly of testicular feminisation with true hermaphroditism, is discussed.